Minimum Inhibitory Concentration of Ethanol Extract of Vernonia amygdalina Delile. against Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus cereus by Disc Diffusion - Putri, Amalia Eka; Ginaris, Rifkarosita Putri; Indrayati, Lyna Lestari (PCJN: Pharmaceutical and Clinical Journal of Nusantara, 2025)
Diarrhea remains a major global health challenge caused by pathogenic bacteria including Escherichia coli, Salmonella typhi, Staphylococcus aureus, and Bacillus cereus. African leaf (Vernonia amygdalina Delile.) contains bioactive compounds such as flavonoids, saponins, tannins, and alkaloids with recognized antibacterial properties. This study determined the Minimum Inhibitory Concentration (MIC) of ethanol extract of V. amygdalina prepared by Ultrasonic-Assisted Extraction (UAE) at three extraction times (5, 15, and 30 minutes) against four diarrhea-causing bacteria using the disc diffusion method. Extraction yields were 8.8%, 10.45%, and 11.9% for UAE at 5, 15, and 30 minutes, respectively. Antibacterial testing at concentrations ranging from 300 to 1.56 mg/mL demonstrated predominantly moderate inhibition zones (5–10 mm), with some concentrations reaching the strong category (10–20 mm). The MIC for B. cereus and S. aureus was 1.56 mg/mL across all extraction times. For S. typhi, the MIC was 1.56 mg/mL (5 and 30 min UAE) and 12.5 mg/mL (15 min UAE). For E. coli, the MIC was 6.25 mg/mL (5 min UAE) and 1.56 mg/mL (15 and 30 min UAE). One-way ANOVA confirmed statistically significant differences among concentrations (p < 0.05). The 30-minute UAE produced the highest yield and generally superior antibacterial activity, supporting its selection as the optimal extraction condition. These findings highlight the potential of V. amygdalina ethanol extract as a natural antibacterial agent for diarrheal disease management.